Core self-evaluations, job satisfaction, transformational and servant leadership model in the Roman Catholic education system / Ginavee F. Dapula and Mary Caroline N. Castano - Dapula, Ginavee F.; Castano, Mary Caroline N. (Penerbit UiTM (UiTM Press), 2017)
Core self-evaluations, effective leadership styles and employee job satisfaction are essential factors for organizational success. This paper aims to determine the relationship of the leader’s core self-evaluations, transformational leadership and servant leadership styles to their follower’s job satisfaction in selected Parochial Schools in Manila, Philippines under the Roman Catholic Education System. The respondents were selected according to certain criteria. Descriptive correlational design was used. In total, 308 individuals from the teaching and non-teaching personnel participated. The data were collected using survey questionnaires. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Research findings revealed that a positive relationship exists between leader’s core self-evaluations and transformational leadership; core self-evaluations to servant leadership; transformational leadership to job satisfaction; and servant leadership to job satisfaction. These relationships are statistically significant. The relationship of the leader’s core self-evaluations to the follower’s job satisfaction indicated a direct effect but were statistically non-significant on the basis of its p-value. The major contribution of the current study is to extend the limited literature regarding the antecedents of the four (4) selected variables. The researcher recommends to the school leaders to create a motivating environment through a more transformational and servant leadership behavior that will enhance their follower’s work satisfaction.